Reductions in virological failure and drug resistance in Chinese antiretroviral-treated patients due to lamivudine-based regimens, 2003–12. (7th April 2015) - Xing, Hui; Ruan, Yuhua; Hsi, Jenny H.; Kan, Wei; Liao, Lingjie; Leng, Xuebing; Wang, Jing; He, Cui; Shao, Yiming; ,
Abstract: Background: China's National Free Antiretroviral Treatment Program (NFATP) has significantly scaled up and standardized treatment since 2008. Meanwhile, no study worldwide has examined on a large scale the effects of rapid ART programme scale-up on treatment outcomes in resource-limited settings. Methods: We used China's national HIV drug resistance (HIVDR) surveillance database to determine virological failure, acquired drug resistance and poor adherence rates after 12–15 months of first-line ART. A total of 2252 patients were examined, with 1431 patients having initiated ART before 2008 and 821 since 2008. Findings: Since 2008, virological failure at 12–15 months of treatment improved from 26.6% to 12.1%, and HIVDR rates also significantly decreased from 15.4% to 5.4%. However, these successes are strongly associated with the standardized use of lamivudine-based regimens in place of didanosine-based regimens. Patients who initiated lamivudine-based regimens before 2008 showed significant improvement in adherence [missed doses adjusted OR (AOR), 0.65; 95% CI, 0.45–0.96], virological failure (AOR, 0.29; 95% CI, 0.22–0.39) and HIVDR outcomes (AOR, 0.29; 95% CI, 0.20–0.42) compared with those who initiated didanosine-based regimens. Meanwhile, among only patients on lamivudine-based regimens, no significant changes were observed between those who initiated before 2008 and those who initiated since 2008. Conclusions: China's NFATP has been largely successful throughout the scale-up, with an overall reduction in virological failure and HIVDR. However, excluding the effect of lamivudine-based regimens, it remains crucial for the programme to improve patient adherence and quality of care, particularly in key vulnerable populations such as those infected through injecting drug or blood routes.